2006
DOI: 10.1139/w05-123
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and taxonomic characterization of bacteria associated with the crucifer root maggot (Delia radicum)

Abstract: The crucifer root maggot, Delia radicum, is an important pest of cruciferous crops; however, little is known about its digestive biochemistry or resident gut microbiota. A culturing approach was used to survey the types of micro organisms associated with eggs, midgut, and faeces of larvae feeding on rutabaga. All bacteria isolated from the midgut and faecal materials were Gram-negative bacilli. Nine types of culturable bacteria were identified within the midgut based on analysis of 60 kDa chaperonin sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…It was also observed that the emission of sulphur containing compounds from plant roots may depend on De. radicum larvae themselves, bacteria and/or the plant material that can be present in their gut [102], [112]. The importance of transcription of genes and/or activation of enzymes has been reported for the production of sulfides in plants [113].…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the emission of sulphur containing compounds from plant roots may depend on De. radicum larvae themselves, bacteria and/or the plant material that can be present in their gut [102], [112]. The importance of transcription of genes and/or activation of enzymes has been reported for the production of sulfides in plants [113].…”
Section: Discussionmentioning
confidence: 99%
“…D. radicum has associated gut microbial symbionts, which may be bacteria, yeast or protozoa that are assumed to enrich the nutritional value of the food by providing essential vitamins and amino acids or by digesting refractory plant materials. However, little is known about its digestive biochemistry, the source of these organisms and the maintenance between generations (Lukwinski et al 2006). It is important to notice then, that for this system, the effects of root herbivory cannot be fully separated from the effects of the microorganisms associated to D. radicum .…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note however, that for D. radicum and related species the effects of root herbivory can not be fully separated from the effects of microorganisms directly and indirectly associated with them. It is reported that D. radicum possesses microorganisms in the alimentary tract that contribute to host nutrition directly as a food source as well as by providing increased digestive potential (Lukwinski et al 2006). Moreover, the damage caused in the roots as a consequence of feeding provides a point of entry for subsequent infection by endemic root rot pathogens (Soroka et al 2004).…”
Section: Volatilesmentioning
confidence: 99%
“…3.3, 3.5 and 3.6). Moreover, D. radicum larvae contain a highly diverse gut microflora that helps them to infest and digest the recalcitrant plant material they feed on; several of these gut bacteria are closely related to sulfide producing bacteria found in soils [119]. Indeed, larvae on sand emitted more sulfides than pure sand, but the emission levels per larva were relatively low compared to the emissions recorded from infested roots.…”
Section: Discussionmentioning
confidence: 99%
“…3.9). Therefore, D. radicum larvae themselves, or the plant material and bacteria that can be found in their alimentary tract or frass [119] may contribute to the signal detected at those masses during the infestation experiments. However, the emission levels of these masses from the cuvettes with the larvae were very low, despite the fact that there were 4 to 5 times more larvae in a much smaller volume than were added to the plant roots.…”
Section: Biogenic Source Of the Sulfur Containing Volatilesmentioning
confidence: 99%